A Novel Regulatory Cascade Involving BluR, YcgZ, and Lon Controls the Expression of Escherichia coli OmpF Porin - Duval, Valérie; Foster, Kimberly; Brewster, Jennifer; Levy, Stuart B. (Frontiers in Microbiology, 2017)
In Escherichia coli, OmpF is an important outer membrane protein, which serves as a passive diffusion pore for small compounds including nutrients, antibiotics and toxic compounds. OmpF expression responds to environmental changes such as temperature, osmolarity, nutrients availability and toxic compounds via complex regulatory pathways involving transcriptional and post-transcriptional regulation. Our study identified a new regulatory cascade that controls the expression of OmpF porin. This pathway involves BluR, a transcriptional regulator repressing the expression of the ycgZ-ymgABC operon. We showed that BluR was responsible for the temperature-dependent regulation of the ycgZ-ymgABC operon. Furthermore, our results showed that independent expression of YcgZ led to a decreased activity of the ompF promoter, while YmgA, YmgB and YmgC expression had no effect. We also determined that YcgZ accumulates in the absence of the Lon protease. Thus, mutation in bluR leads to de-repression of ycgZ-ymgABC transcription. With a second mutation in lon, YcgZ protein accumulates to reach levels that do not allow increased expression of OmpF under growth conditions that usually would i.e. low temperature. With BluR responding to blue-light and temperature, this study sheds a new light on novel signals able to regulate OmpF porin.